Isolation and in vitro antagonistic activity of indigenous rhizosphere Trichoderma against Colletotrichum cf. musae causing banana anthracnose - NGUYEN TRUNG TRUC; KHOA DANG DANG; QUACH VAN CAO THI; NGUYEN LE YEN NHI; NGUYEN MINH TRONG; LE VAN UT (Society for Indonesian Biodiversity, 2026)
Abstract. Truc NT, Dang KD, Thi QVC, Nhi NLY, Trong NM, Ut LV. 2026. Isolation and in vitro antagonistic activity of indigenous rhizosphere Trichoderma against Colletotrichum cf. musae causing banana anthracnose. Biodiversitas 27 (5): d270534. https://doi.org/10.13057/biodiv/d270534. Banana is a high-yielding and economically important export crop. However, anthracnose caused by Colletotrichum spp. is a causative agent that reduces fruit quality and shelf life. Trichoderma is known for its antagonistic activity against a wide range of plant pathogens, including Colletotrichum species. The aim of the present study was to isolate Trichoderma isolates from rhizosphere soil samples and to evaluate their antagonistic activity against Colletotrichum sp. In the present study, ten Colletotrichum isolates were obtained and identified from banana fruits showing anthracnose symptoms. Among them, isolate C12.1 was the most frequently isolated and identified as Colletotrichum cf. musae. Trichoderma species were isolated from 15 rhizosphere soil samples of banana plants. The results showed that a total of 16 Trichoderma isolates were isolated from 15 soil samples from banana plants collected from different areas in Vinh Long Province. All Trichoderma isolates exhibited strong antagonistic activity against Colletotrichum sp. Notably, isolates TC1, TC2, TC5, TC9, TC10, and TC11 demonstrated the highest in vitro inhibition of mycelial growth, ranging from 80.61% to 87.88%. Among these, isolate TC5, which exhibited both strong inhibitory activity (87.88%) and significant extracellular enzyme production, was selected for PCR amplification and sequencing of the internal transcribed spacer (ITS) region. Isolate TC5 was likely the closest relative to Trichoderma hamatum and was identified as T. hamatum. In addition, six selected Trichoderma isolates were qualitatively assessed for extracellular enzyme production. All tested isolates were positive for cellulase, amylase, β-1,3-glucanase, and chitinase. The production of these enzymes highlights their role in mycoparasitism and supports the potential of Trichoderma isolates as effective biocontrol agents. Although the findings demonstrate promising antagonistic potential, the results are currently limited to in vitro assays and qualitative enzyme detection. Therefore, further studies under in vivo conditions are required to validate their efficacy before practical field application.